EXPERT HUMAN RESOURCES DECISION MAKERS: UNCOVERED IN CONTEXT - Dell, Jeffrey Cole Benny (My University, 2009)
This thesis investigates how human resources (HR) experts make decisions within the context of their organization. It uses the Naturalistic Decision Making model (NDM) to best determine the processes deployed by 20 HR experts. The HRM Practices Model (Subramony & Feinauer, working paper) is supported and extended by the qualitative data collected in this study. Two major stages are added to the implementation process: execution and process embedment. Additionally, the implications for the education system and preparation for the next generation are discussed.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science - Psychology Industrial Organizational
Keywords: Knowledge management; Personnel management; Career development; Strategic planning